Prevalence of chronic obstructive pulmonary disease among non-smokers in rural areas of Lucknow district, Uttar Pradesh, India - Bage, Rowanti N.; Singh, Shivendra K.; Srivastava, Anand; Manar, Manish; Kushwaha, Sonam; Swaroop, Vibha; Rai, Ambrish K. (International Journal Of Community Medicine And Public Health, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is a chronic progressive disease of the airways and lung parenchyma and the risk factors include both genetic and environmental factors. Tobacco smoking has remained the most important risk factor associated with it. The occurrence of COPD in non-smokers is not widely appreciated, even though its relative burden is higher in developing countries than developed countries. There is limited information on the risk factors associated with spirometrically confirmed COPD in non-smokers in the general population and more data from population-based studies are needed. Hence, the objective of this study was to determine the prevalence of COPD and associated risk factors among non-smokers in rural areas of Lucknow district, Uttar Pradesh, India. Methods: This cross-sectional study with multi-stage random sampling was conducted among 552 non-smoking participants aged 18 years and above in rural areas of Lucknow. It was conducted using pre-designed questionnaire for data collection. COPD assessments were done using a combination of clinical history and portable spirometry. Data collected was analysed using SPSS 23.0 version. Results: FEV1/FVC <0.7 was used to define COPD which yielded a prevalence of 8.5 percent among non-smoking participants. Gender, occupation, type of family, presence of ex-smoker, presence of dampness and livestock in the house were the risk factors that showed statistically significant association with COPD. Conclusions: The higher prevalence noted in this study highlights the need for enhanced community-based screening programme for secondary prevention of COPD among adults.